Modeling of Bioactive Compound Content of Different Tea Bags: Effect of Steeping Temperature and Time - Yildirim, Rusen Metin; Ozulku, Gorkem; Toker, Omer Said; Baslar, Mehmet; Durak, M. Zeki; Sagdic, Osman (WILEY, 2017)
In the present study, it was aimed to investigate functional properties (total phenolic, flavanoid and anthocyanin contents and 2,2-diphenyl-1-picrylhydrazyl [DPPH] activity) of different tea bags, namely blackberry, rosehip and bilberry steeped at different temperatures (60, 75 and 90C) for different periods (2-12 min) with 2-min intervals. Both the temperature and time period levels significantly affected all of the functional properties mentioned. Increasing temperature and time period of steeping process generally increased total phenolic, flavonoid and anthocyanin contents and DPPH activity of the all samples. Change in bioactive compound concentration with respect to time was successfully modeled with different models (First order rate, Weubillian and Peleg models). All of the developed models could be used to describe relation between bioactive compound content of tea samples and steeping time. According to the results of the present study, steeping temperature and period should be considered to improve functionality of tea samples. Practical ApplicationsTea bags are consumed due to their functional properties and specific taste over the world since they are easily prepared in very short times. Functional properties of them could be improved by adjusting steeping conditions such as temperature and time. The findings of the present study should be considered in order to increase bioactive compound content of tea samples.
Keywords: ANTIOXIDANT ACTIVITY; BLACKBERRY EXTRACT; PHENOLIC-COMPOUNDS; IN-VITRO; ROSA; CAFFEINE; IDENTIFICATION; DYSFUNCTION; CAPACITIES; INFUSION; Food Science & Technology